A Case of Continuous Negative Pressure Wound Therapy for Abdominal Infected Lymphocele after Kidney Transplantation - Marco Franchin; Matteo Tozzi; Gabriele Soldini; Gabriele Piffaretti (Case Reports in Transplantation)
Lymphocele is a common complication after kidney transplantation. Although superinfection is a rare event, it generates a difficult management problem; generally, open surgical drainage is the preferred method of treatment but it may lead to complicated postoperative course and prolonged healing time. Negative pressure wound therapy showed promising outcomes in various surgical disciplines and settings. We present a case of an abdominal infected lymphocele after kidney transplantation managed with open surgery and negative pressure wound therapy.